O pochodzeniu języka - Schmidt, Gerhart (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2012)
What is the origin of language? Herder says, the word makes the man from the animal, but it should be a natural process. The author writes about the pointing at somebody/something as distinction between “being” and “nothing”. This action gets more and more symbolic. The pointing turned into names and grammatical structure. It becomes at last language
Keywords: Herder; Origine of language as pointing at sb/sth